'Untitled' - R. Ferrell (Law Text Culture, 1998)
When an artist offers a work as 'untitled', it prevents a certain kind of knowledge; the knowledge given in advance of the effects of the work, and apart from the affects that it gives rise to. The artwork which witholds being known in this a priori way forces instead an interpretation without benefit of the artist's legislation as to its meaning. An interpretation without the force of law. The untitled work, in this way, brings us into the vicinity of the creation of fact and value. It foregrounds the making of understanding, and therefore of knowledge, as an aesthetic event. This paper connects the questions of land, law and art through the double sense of a 'title'; a claim to ownership of land, a claim to know the meaning of the work of art.